The Augmented Reality 3D Object Augmented Reality: Augmented Reality 3D Object with EasyAR and Unity 3D - Feriyadi, Nur (Puslitbang Kopertip Indonesia, 2018)
The use of communication and information technology is currently growing very rapidly, one of which is augmented reality. Augmented reality is a technology that combines the real world and the virtual world. In making this augmented reality using software Unity3D and Easyar. The author's job is to add augmented reality 3D. In the development of this application using dynamic scrum method. This app is complement to the yearbook. Usefulness of this application provides information about Senior High School Taruna Nusantara such as vision of mission, address, and landmark of SMA Taruna Nusantara and also mars song from Senior High School Taruna Nusantara..